MOTIF KEPEMILIKAN SMARTPHONE PADA MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Sri Ngayomi Widya Astuti; Raudah Zaimah Dalimunthe (Jurnal Penelitian Bimbingan dan Konseling, 2017)
Ownership of a smartphone on studentsbacked by motive rational and emotional.The purpose of research carried out for getting on information about motive ownership of a smartphone on studentsBK FKIP UMSU. This is considered necessaryto motive for having influence a significant impact on decision making behavior the purchase of a product, so that the result of research is expected can have become guidelines for students before do purchases in stores.Methods used in this research is descriptive quantitative with the approach .Meanwhile , the research sample are 172 there person and college students BK FKIP UMSU drawn based on proportional technique random sampling. An instrument that is used is the scale of motive ownership of a smartphone and analyzed by the use of the criteria for assessing which thedata reference to the boundaries that put forward by Azwar ( 2012 ).As for the result of the research, a motive rationaland emotional ownership of a smartphonein student BK FKIP UMSU are at the level of high. Keywords : Motive,Smartphone